Bandwidth enhancement and circular polarization microstrip antenna using L slot and rectangular parasitic stacked - Surjati, Indra; Alam, Syah; Sari, Lydia; Ningsih, Yuli Kurnia; Astuti, Dian Widi; Firmansyah, Teguh; Zakaria, Zahriladha; Shairi, Noor Azwan (Sumy State University, 2022)
This study proposes a microstrip antenna with L slot that is optimized using parasitic patches. The addition of parasitic elements aims at enhancing the bandwidth of the proposed antenna. Parasitic elements were added using two types of FR-4 substrate, which were stacked. The radiating element was placed in the bottom layer, while the parasitic element was in the top. To produce optimal bandwidth, three models were proposed with different forms of parasitic elements. The best results were shown by model 1 with an impedance bandwidth of 1.3 GHz (2.17-3.47 GHz) or with impedance bandwidth of 52 %. In addition, the proposed antenna design also produced circular polarization with an axial ratio of ≤ 3 dB and a maximum gain of 6.76 dB. The proposed antenna design can be recommended and suitable for use as a receiving antenna in a wireless communication system.